Cross-border everyday lives on the Luxembourg border? An empirical approach: The example of cross-border commuters and residential migrants - Christian Wille; Ursula Roos (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
Luxembourg is characterized by phenomena of mobility that include cross-border commuters and residential migrants. While both groups have been mainly examined from a socioeconomic perspective, this paper adopts a sociocultural approach. We will focus on the question of the extent to which cross-border mobility in everyday life promotes cross-border lifeworlds. This will involve examining people's social contacts at their place of work and/or place of residence as well as the spatial organization of practices of the everyday life of both groups. The paper gives insights into everyday lives at the EU's internal borders, whose organization into nation states is subordinate and at the same time constitutive.
urn:nbn:de:0156-40971154; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Border studies; residential migration; cross-border commuting; integration; Luxembourg